Study of neonatal outcome in relation to maternal nutrition and anthropometry - Sanghvi, Jyoti; Patel, Ankita (International Journal of Contemporary Pediatrics, 2016)
Background: Neonatal mortality contributes to over 64% of the infants deaths and most of these deaths occur during first week of life. Of the various causes of infant mortality, birth weight is one of the important factors for the survival, normal growth and development of child. Methods: This one year hospital based case control study was undertaken to find out the proportion of low birth weight babies in institutional deliveries and to find out the association between various socio-demographic and maternal factors with low birth weight deliveries in study population. Data analysis was done using SPSS version 15.0. One way Anova and Chi square test was used. Results: Out of total 100 live new-borns, 46 were low birth weight babies. Significant associations were found between maternal height< 150 cm, maternal weight gain and maternal pre partum body weight with low birth weight babies. Significant correlation was also seen between the age <20 yrs and >30 yrs of age, parity and socioeconomic status with low birth weight. Conclusions: This study provides baseline information from the tertiary care hospital in this region. Strengthening of the maternal health program focusing on maternal nutrition and iron and folic acid supplementation during antenatal period and nutrition education to facilitate better weight gain during adolescent period is required.